Bilateral ultrastaging of sentinel lymph node in cervical cancer: Lowering the false-negative rate and improving the detection of micrometastasis - Cibula, David; Abu-Rustum, Nadeem R; Dusek, Ladislav; Slama, Jiri; Zikán, Michal; Zaal, Afra; Sevcik, Libor; Kenter, Gemma; Querleu, Denis; Jach, Robert; Bats, Anne-Sophie; Dyduch, Grzegorz; et al. (Gynecologic oncology, 2012)
OBJECTIVE: To evaluate the sensitivity of sentinel node (SN) ultrastaging and to define parameters that may reduce the overall false-negative rate in women with early-stage cervical cancer. METHODS: We analyzed data from a large retrospective multicenter cohort group with FIGO stages IA-IIB cervical cancer in whom at least one SN was identified and systematic pelvic lymphadenectomy was uniformly performed. All who were SN negative by initial evaluation were subjected to ultrastaging. RESULTS: In all, 645 patients were evaluable. SN were detected bilaterally in 72% of cases and unilaterally in 28%. Patients with optimal bilateral SN detection were significantly more likely to have any metastasis detected (33.3% vs. 19.2%; P<0.001) as well as micrometastasis detected in their SN (39.6% vs. 11.4%). SN ultrastaging resulted in a low overall false-negative rate of 2.8% (whole group) and an even lower false-negative rate of 1.3% for patients with optimal bilateral mapping. Patients with false-negative SN after ultrastaging had a higher prevalence of LVSI and more frequent unilateral SN detection. Sensitivity of SN ultrastaging was 91% (95% CI: 86%-95%) for the whole group and 97% (95% CI: 91%-99%) in the subgroup with bilateral SN detection. CONCLUSION: These data confirm previous observations that optimal bilateral SN detection substantially decreases the false negative rate of SN ultrastaging and increases detection of micrometastasis. In patients with bilateral SN detection, the sensitivity of SN ultrastaging is not reduced in more advanced stages of the disease. SN mapping and ultrastaging should become standard practice in the surgical management of early-stage cervical cancer.
Keywords: mikrometastázy; False Negative Reactions; Humans; lidé středního věku; kohortové studie; Female; Aged; falešně negativní reakce; nádory děložního čípku; senioři; lidé; Lymphatic Metastasis; lymfatické metastázy; biopsie sentinelové lymfatické uzliny; Cohort Studies; staging nádorů; ženské pohlaví; Sentinel Lymph Node Biopsy; Middle Aged; Retrospective Studies; Uterine Cervical Neoplasms; retrospektivní studie; Neoplasm Staging; Neoplasm Micrometastasis